Benzoic acid–4-{(1E)-[(E)-2-(pyridin-4-ylmethylidene)hydrazin-1-ylidene]methyl}pyridine (2/1) - Hadi D. Arman (Acta Crystallographica Section E, 2010)
In the title co-crystal, C12H10N4·2C7H6O2, the complete 4-pyridinealdazine molecule is generated by a crystallographic centre of inversion. In the crystal, molecules are connected into a three component aggregate via O—H...N hydrogen bonds. As both the benzoic acid [O—C—C—C torsion angle = 174.8 (2)°] and 4-pyridinealdazine (r.m.s. deviation of the 16 non-H atoms = 0.041 Å) molecules are almost planar, the resulting three-component aggregate is essentially planar. The crystal packing comprises layers of the three-component aggregates of alternating orientation stacked along the b axis; the connections between the molecules are of the types C—H...π and π–π [pyridine–benzene centroid–centroid distance = 3.787 (4) Å].